The Endocrine Heart: Natriuretic Peptides and Oxygen Metabolism in Cardiac Diseases - Arjamaa Olli (Elsevier Inc., 2022)
Circulating natriuretic peptides are widely used as tools in the diagnosis and follow-up of cardiac diseases, and their use has been increasing throughout other medical branches. After 40 years and more than 40,000 publications, their function in healthy human adults of reproductive age appears to remain confusing-with every physiology and pharmacology textbook telling a different story. In cardiology, mechanical load upon the heart is generally regarded as the condition that regulates the synthesis and release of natriuretic peptides. The key issue in cardiology remains how mechanical activity and oxygen consumption are related, and yet no published paper has shown that mechanical load does not increase oxygen consumption, as wall tension is a major determinant of myocardial oxygen consumption. However, this relationship has been largely neglected in studies on natriuretic peptides. Based on published papers, an outline is presented of how oxygen metabolism, related to mechanical stress, could play an important role in the pathophysiology of natriuretic peptides. The natriuretic peptide system might enhance oxygen transport by causing diuresis, natriuresis, and water transfer from the intra- to extravascular space, resulting in volume contraction and hemoconcentration, thus indirectly promoting the transfer of oxygen into tissues and organs. Mechanical stress and oxygen consumption are 2 sides of the same coin. The relationship between mechanical stress and oxygen metabolism, in the particular case of natriuretic peptides, represents a new avenue for clinical studies and will better explain the results of studies that have been published previously.